Modulation of Macrophages by In Situ Ligand Bridging (Adv. Funct. Mater. 16/2023). (18th April 2023) - Kim, Seong Yeol; Thangam, Ramar; Kang, Nayeon; Hong, Hyunsik; Kim, Chowon; Lee, Sungkyu; Son, Subin; Lee, Hyun‐Jeong; Tag, Kyong‐Ryol; Min, Sunhong; Jeong, Daun; Hwang, Jangsun; et al.
Abstract : Macrophage Adhesions In article number 2215166, Heemin Kang, Jong Seung Kim, and co‐workers report the magnetic control of bridging and non‐bridging between magnetic RGD‐coated nanomaterials and non‐magnetic RGD nanomaterials. This variable RGD bridging in situ temporally modulates the recruitment, integrin binding, and adhesion structure assembly of host macrophages that determine their functional pro‐inflammatory or pro‐healing immunoregulation.